PENGARUH PENGGUNAAN MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 141 LILINA AJANGALE KABUPATEN BONE - Sudarto, Sudarto; Sitti Jauhar,; Fatimah Mardani, (Jurnal Cakrawala Ilmiah, 2025)
This study is a pre-experimental study that aims to determine whether the use of the Active Learning model in type of Role Reversal Question has an effect or not in improving the learning outcomes of students in IPAS of the 4th Grade at SD Negeri 141 Lilina Ajangale. The research design used is One-Group Pretest-Postest Design. The population in this study were all of the 4th Grade students at SD Negeri 141 Lilina Ajangale with a sample of 20 students selected based on the saturated sample technique. The data collection technique used was the test technique with a research instrument in the form of a test sheet. The data analysis used was descriptive and inferential statistical analysis. Based on the results of the descriptive statistical analysis, the average pretest was of 42.5 and the average posttest was of 78.5. The data obtained were then analyzed using the paired sample t-test with a significance level of 0.05. From the results of data analysis obtained tcount 20.429 > ttable 2, 093 then H0 is rejected H1 is accepted which means that there is a significant influence of the Active Learning model in type of Role Reversal Question to the the learning outcomes of 4th students at SD Negeri 141 Lilina Ajangale Bone Regency. Conclusion: the use of the Active Learning model type Role Reversal Question has a significant effect to improving the IPAS learning outcomes of the 4th Grade students at SD Negeri 141 Lilina Ajangale Bone Regency